Oxidative stability and ignition quality of algae derived methyl esters containing varying levels of methyl eicosapentaenoate and methyl docosahexaenoate - Bucy, Harrison, author; Marchese, Anthony John, 1967-, advisor; Willson, Bryan D., committee member; Smith, T. Gordon, committee member (Colorado State University. Libraries, 2011)
Microalgae is currently receiving strong consideration as a potential biofuel feedstock to help meet the advanced biofuels mandate of the 2007 Energy Independence and Security Act because of its theoretically high yield (gallons/acre/year) in comparison to current terrestrial feedstocks. Additionally, microalgae also do not compete with food and can be cultivated with wastewater on non-arable land. Microalgae lipids can be converted into a variety of biofuels including fatty acid methyl esters (e.g. FAME biodiesel), renewable diesel, renewable gasoline, or jet fuel. For microalgae derived FAME, the fuel properties will be directly related to the fatty acid composition of the lipids produced by the given microalgae strain. Several microalgae species under consideration for wide scale cultivation, such as Nannochloropsis, produce lipids with fatty acid compositions containing substantially higher quantities of long chain-polyunsaturated fatty acids (LC-PUFA) in comparison to terrestrial feedstocks. It is expected that increased levels of LC-PUFA will be problematic in terms of meeting all of the current ASTM specifications for biodiesel. For example, it is known that oxidative stability and cetane number decrease with increasing levels of LC-PUFA. However, these same LC-PUFA fatty acids, such as eicosapentaenoic acid (EPA: C20:5) and docosahexaenoic acid (DHA: C22:6) are known to have high nutritional value thereby making separation of these compounds economically attractive. Given the uncertainty in the future value of these LC-PUFA compounds and the economic viability of the separation process, the goal of this study was to examine the oxidative stability and ignition quality of algae-based FAME with varying levels of EPA and DHA removal. Oxidative stability tests were conducted at a temperature of 110 °C and airflow of 10 L/h using a Metrohm 743 Rancimat with automatic induction period determination following the EN 14112 Method from the ASTM D6751 and EN 14214 Standards, which call for induction periods of at least three hours and six hours, respectively. Derived Cetane Number testing was conducted using a Waukesha FIT following the ASTM D7170 Method. Tests were conducted with synthetic algal oil blends manufactured from various sources to match the fatty acid compositions of several algae strains subjected to varying removal amounts of roughly 0 - 100 percent LC-PUFA. In addition, tests were also conducted with real algal methyl esters produced from multiple sources. The bis-allylic position equivalent (BAPE) was calculated for each fuel sample to quantify the level of unsaturation. The induction period was then plotted as a function of BAPE, which showed that the oxidative stability varied exponentially with the amount of LC-PUFA. The results suggest that removal of 45 - 65 percent of the LC-PUFA from Nannochloropsis-based algal methyl esters would be sufficient for meeting existing ASTM specifications for oxidative stability and 75 - 85 percent removal would be needed to meet the EN specification. The oxidative stability additive tert-butylhydroquinone (THBQ) was found to increase Nannochloropsis-based algal methyl esters' oxidative stability to ASTM and EN specifications at only 0.03 percent and 0.06 percent additions by mass, respectively, when no LC-PUFA was removed. The ignition quality tests showed that the Derived Cetane Number varied linearly with BAPE and the algae formulations were found to pass the ASTM cetane specification of 47 only if all the LC-PUFA were removed.
Keywords: algae; biodiesel; DHA; EPA; ignition quality; oxidative stability